2011
DOI: 10.1007/s10753-011-9372-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammatory Processes by Leaves Extract from Clusia nemorosa Both In Vitro and In Vivo Animal Models

Abstract: The present study was carried out to investigate the anti-inflammatory effect of the hexane extract of the leaves from Clusia nemorosa G. Mey, called HECn, using carrageenan-induced mice pleurisy and cotton pellet-induced mice granuloma. Additionally, the ability of HECn to affect both neutrophil migration as viability was investigated by use of the Boyden chamber assay and flow cytometry, respectively. The HECn significantly inhibited exudation, total leukocytes and neutrophils influx, as well as TNFα levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
14
0
4
Order By: Relevance
“…27 Therefore, it has been suggested that the inhibition of prostaglandin synthesis is remarkably efficient as an antinociceptive mechanism in visceral pain. 28 In our study, the two doses of extract (200 mg/kg and 400 mg/kg) had increased the reaction time in dose-dependent manner; 400 mg/kg of MI extract had exhibited anti-nocioceptive effect to thermal stimulus at 120 mins, which is comparable to standard drug tramadol.…”
Section: Discussionsupporting
confidence: 51%
“…27 Therefore, it has been suggested that the inhibition of prostaglandin synthesis is remarkably efficient as an antinociceptive mechanism in visceral pain. 28 In our study, the two doses of extract (200 mg/kg and 400 mg/kg) had increased the reaction time in dose-dependent manner; 400 mg/kg of MI extract had exhibited anti-nocioceptive effect to thermal stimulus at 120 mins, which is comparable to standard drug tramadol.…”
Section: Discussionsupporting
confidence: 51%
“…This leukocytes recruitment, mainly neutrophils, to the sites of inflammation enables an efficient defensive action against foreign pathogens [67,68]. A panel of diverse stimuli, especially pathogen-associated molecular pattern (PAMPs) and damage-associated molecular pattern (DAMPs) molecules, activates professional tissue-resident sentinel cells, such as macrophages and mast cells [69,70]. These sentinel cells release proinflammatory mediators [e.g., interleukin (IL)-1b and tumor necrosis factor (TNF)], and neutrophil-active chemoattractants (e.g., chemokines and lipid mediators), initiating the recruitment of neutrophils into the tissue by diverse actions.…”
Section: Inhibition Of Inflammatory Angiogenesismentioning
confidence: 99%
“…The writhing test has long been used as a screening tool for assessing the analgesic properties of new substances (Collier et al, 1968). Intraperitoneal administration of acetic acid induce abdominal writhing and involves the increase in cyclooxygenase (COX), lipoxygenase (LOX), prostaglandins (PGs), histamine, serotonin, bradykinin, substance P, IL-1β, IL-8, TNF-α in the peritoneal cavity (Farias et al, 2011). These agents provoke a very stereotyped behavior in the mice which is characterized by abdominal contractions, movements of the body as a whole and twisting of dorso-abdominal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, parallel group of animals was pre-treated (30 min before pleurisy induction) with indomethacin (10 mg/kg, i.p.) and 4 h later the same inflammatory parameters were evaluated (Farias et al, 2011).…”
Section: Carrageenan-induced Pleurisymentioning
confidence: 99%